STATE OF THE MATRIX METALLOPROTEINASES AND THEIR ROLE IN FORMATION OF THE CHRONIC HEART FAILURE IN CHILDREN WITH DILATED CARDIOMYOPATHY - E.N. Basargina; A.G. Gasanov; T.V. Bershova; M.I. Bakanov; A.P. Ivanov; O.O. Kupriyanova (Union of pediatricians of Russia, 2009)
The article is devoted to an important section of the pediatric cardiology - dilated cardiomyopathy (DCMP). This is largely due to the spread of the given disease, its possible progress and tendency to the formation of the chronic heart failure (CHF). The progress in the research of the DCMP'accompanied CHF formation and development processes is the studies of the extracellular matrix status (EM), which is defined by the activity of the matrix metalloproteinases (MMP) and their tissue inhibitors (TIMMP). This article describes the complex clinical and biochemical studies of the serum MMP'1, MMP'2, MMP'9 and TIMMP'1 levels in children with DCMP at different stages of the illness course. MMP and their inhibitor concentration were defined by means of the enzyme'linked immunosorbent assay (ELISA). Based on the results from the morphofunctional studies and data of the biochemical analyses, the authors determined the importance of changes in the isomeric EM composition pertaining to the disturbances of the systolic and diastolic functions, as well as in heart remodeling for such children.Key words: chronic heart failure, dilated cardiomyopathy, extracellular matrix, matrix metalloproteinases, tissue inhibitors of the matrix metalloproteinases.